Attrition, mental health and student support in engineering education: the Engineering Futures Project. (20th November 2020) - Andrews, Jane; Clark, Robin; Phull, Sukhvinder
This paper deals with issues surrounding student attrition in engineering education. Looking beyond the traditional markers associated with student attainment, and adopting an action research approach, the "Engineering Futures Project" aimed to tackle an attrition rate in a faculty of engineering that was twice the university average. An algorithm was developed and students 'at risk' of not progressing identified. Such students were then contacted individually and offered intensive support and guidance from a member of the project team.Working with academics on a one-to-one basis, students were encouraged to reflect on why they felt they were at risk of not progressing on to the next level of their course. One of the surprising outcomes was that the majority of students indicated they had experienced considerable difficulties with their mental health in the previous 12 months. This, together with a number of other individual issues, impacted their studies. Taking account of the students' perspectives, the project team developed and put in place two distinctive support pathways; one focusing on 'wellbeing', the other on "academic support'. Each individual student was given time and assistance to develop their own pathways. Although resource intensive, the Engineering Futures Project was a marked success, drastically reducing attrition and making a notable difference at both the individual and faculty level.